7-(-2k+4)-6=7k-20

Simple and best practice solution for 7-(-2k+4)-6=7k-20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(-2k+4)-6=7k-20 equation:


Simplifying
7 + -1(-2k + 4) + -6 = 7k + -20

Reorder the terms:
7 + -1(4 + -2k) + -6 = 7k + -20
7 + (4 * -1 + -2k * -1) + -6 = 7k + -20
7 + (-4 + 2k) + -6 = 7k + -20

Reorder the terms:
7 + -4 + -6 + 2k = 7k + -20

Combine like terms: 7 + -4 = 3
3 + -6 + 2k = 7k + -20

Combine like terms: 3 + -6 = -3
-3 + 2k = 7k + -20

Reorder the terms:
-3 + 2k = -20 + 7k

Solving
-3 + 2k = -20 + 7k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-7k' to each side of the equation.
-3 + 2k + -7k = -20 + 7k + -7k

Combine like terms: 2k + -7k = -5k
-3 + -5k = -20 + 7k + -7k

Combine like terms: 7k + -7k = 0
-3 + -5k = -20 + 0
-3 + -5k = -20

Add '3' to each side of the equation.
-3 + 3 + -5k = -20 + 3

Combine like terms: -3 + 3 = 0
0 + -5k = -20 + 3
-5k = -20 + 3

Combine like terms: -20 + 3 = -17
-5k = -17

Divide each side by '-5'.
k = 3.4

Simplifying
k = 3.4

See similar equations:

| 14y+19=2y+127 | | (2x-1)/3=4 | | (2x-1)/=4 | | 3y-14=y | | (2x-1)/34 | | 3y-18=y | | 18/6=6/w | | 10h-20+4h-5= | | 3xy-xy+4xy= | | 2cos^3x-cos^2x+2cosx+sqrt(3)=0 | | -2(4)-y=2 | | Z+1=2x-z | | 17=3(x+5) | | 20a^3=-18a^2+18a | | 0=-2x^2+2x+1 | | 10=y^1/4*x^1/4 | | 4(x-2)=-6 | | 6(x-2)=6x-3 | | (5x+5)=180 | | 3x-9x+1=2(1-3x)-1 | | 18+4(w-1)=5w+6 | | 1+3x=2x-5x+1 | | 3(1+2x)=6x+1 | | f(x)=2y^3-5y^2-3y | | -1.5(x-38)+4.7x+1.4(x+16.5)= | | 1+3x=2x-5x | | 19x+8(x-5)=10(4x-5) | | 8x+12=8x+4 | | 6u^2-28-16= | | 1-3x=2x-5x+1 | | 3-4x+9=8x+12 | | 2-3x=4x-2 |

Equations solver categories